More financial burden-sharing for developing countries that host refugees - Matthias Lücke; Claas Schneiderheinze (Kiel Institute for the World Economy (IfW), 2017)
The authors call on G20 leaders to extend more predictable and substantial support to lowand- middle-income countries that host refugees, in recognition of the global public good that these countries provide. Together with other high-income countries, G20 countries should fully cover the cost of providing for the basic and social needs of refugees. They should also help to expand public services and infrastructure to cover the needs of refugees as well as resident populations. G20 countries should work with host countries to ensure that refugees are granted a firm legal status that promotes their social inclusion and opportunities for employment and entrepreneurship.
Keywords: F22; F53; O15; 330; asylum seekers; refugees; burden-sharing; humanitarian assistance; international public goods; international institutional arrangements